Respiratory and Limb Muscle Dysfunction in COPD - Barreiro, Esther; Gea, Joaquim (Chronic obstructive pulmonary disease, 2015)
In the next decade, Chronic Obstructive Pulmonary Disease (COPD) will be a major leading cause of death worldwide. Impaired muscle function and mass are common systemic manifestations in COPD patients and negatively influence survival. Respiratory and limb muscles are usually affected in these patients, thus contributing to poor exercise tolerance and reduced quality of life (QoL). Muscles from the lower limbs are more severely affected than those of the upper limbs and the respiratory muscles. Several epidemiological features of COPD muscle dysfunction are being reviewed. Moreover, the most relevant etiologic factors and biological mechanisms contributing to impaired muscle function and mass loss in respiratory and limb muscles of COPD patients are also being discussed. Currently available therapeutic strategies such as different modalities of exercise training, neuromuscular electrical and magnetic stimulation, respiratory muscle training, pharmacological interventions, nutritional support, and lung volume reduction surgery are also being reviewed, all applied to COPD patients. We claim that body composition and quadriceps muscle strength should be routinely explored in COPD patients in clinical settings, even at early stages of their disease. Despite the progress achieved over the last decade in the description of this relevant systemic manifestation in COPD, much remains to be investigated. Further elucidation of the molecular mechanisms involved in muscle dysfunction, muscle mass loss and poor anabolism will help design novel therapeutic targets. Exercise and muscle training, alone or in combination with nutritional support, is undoubtedly the best treatment option to improve muscle mass and function and QoL in COPD patients.